Critical Terms in Caribbean and Latin American Thought
XII, 299 p.
Keywords: Through a collection of critical essays, this work explores twelve keywords central in Latin American and Caribbean Studies: indigenismo, Americanism, colonialism, criollismo, race, transculturation, modernity, nation, gender, sexuality, testimonio, and popular culture. The central question motivating this work is how to think—epistemologically and pedagogically—about Latin American and Caribbean Studies as fields that have had different historical and institutional trajectories across the Caribbean, Latin America, and the United States.